2015
DOI: 10.4335/13.3.973-994(2015)
|View full text |Cite
|
Sign up to set email alerts
|

Public Spending Policies and Budgetary Balances: Evidence from Spanish Municipalities

Abstract: Unlike the frequent research that analyzes the effects of various demographic, economic and political factors on fiscal deficits of governments, this research focuses on studying whether certain structures of public spending policies are associated with situations of fiscal imbalances. Using a panel data model with endogenous variables and taking into account various socio-economic factors as instruments, we have observed that the spending policies of Basic public services, Social protection and social promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Previous studies (Brusca et al,2015;Cabaleiro and Buch, 2015;Benito et al, 2012;Gómez and Herrero 2011;Geys and Revelli 2011;García et al 2011;Beland Miralles 2010;Benito et al 2009) have shown that political factors can affect the financial behaviour of governments. In this respect three specific types of variables have been identified: the mayor's profile that of the government and the consolidation of the political environment.…”
Section: Independent Variablesmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies (Brusca et al,2015;Cabaleiro and Buch, 2015;Benito et al, 2012;Gómez and Herrero 2011;Geys and Revelli 2011;García et al 2011;Beland Miralles 2010;Benito et al 2009) have shown that political factors can affect the financial behaviour of governments. In this respect three specific types of variables have been identified: the mayor's profile that of the government and the consolidation of the political environment.…”
Section: Independent Variablesmentioning
confidence: 97%
“…The identification of political factors that are relevant to the risk of local government default is a contribution to previous research in this field (Geys and Revelli, 2011;Gómez and Herrero, 2011;Navarro et al, 2015). Taking into account that the banks are major creditors of local governments, such a contribution should focus on the analysis of bank loans, the high volume of which is of great concern to citizens, voters, taxpayers, financial managers, policymakers, financial institutions and other stakeholders (IMF 2014;Navarro et al 2015;Bastida et al 2015;Cabaleiro and Buch, 2015;Moody's 2013).…”
Section: Measuring the Risk Of Local Government Default By The Basel ...mentioning
confidence: 99%
“…Local politicians' individual characteristics can have an impact on information use (Askim, 2007(Askim, , 2009; Buylen and Christiaens, 2014). The meaning of political ideology has been used as a variable in previous research (Navarro-Galera et al, 2017;Brusca et al, 2015;Cabaleiro-Casal and Buch-Gòmez, 2015;Bastida et al, 2009). In addition to ideology, Askim (2008) considers other individual attributes that are likely to influence the use of information by elected politicians, such as education, political experience and formal political role.…”
Section: Use Of Financial Informationmentioning
confidence: 99%
“…Different theories and their resulting arguments indicate that public outcomes are conditioned by diverse demographic, economic, and political variables that characterize the socioeconomic environment (Sacchi and Salotti 2016; Shelton 2007). Demographic variables such as population, population density, age structure, gender ratio, and immigration (Alesina, Baqir, and Easterly 1999; Concialdi 1999; Delgado, Lago-Peñas, and Mayor 2015; Disney 2007; Lott and Kenny 1999; Mayr 2007; Park 2014; Shelton 2007); economic variables such as economic level and unemployment (Breunig and Busemeyer 2012; Concialdi 1999; Delgado, Lago-Peñas, and Mayor 2015; Shelton 2007; Suzuki and Avellaneda 2018); and political variables such as turnout, political cycle, political fragmentation, government political weakness, and ideology (Alesina and Perotti 1995; Cabaleiro and Buch 2015; Freier and Odendahl 2012; Garmann 2014; Guillamón, Bastida, and Benito 2013; Potrafke 2011; Rogoff 1990; Roubini and Sachs 1989; Shi and Svensson 2006; Suzuki and Avellaneda 2018; Tufte 1978) have been found in the scientific literature to be variables that have effects on public outcomes.…”
Section: Empirical Strategymentioning
confidence: 99%